Formulasi Minyak Angin Aromaterapi Dengan Menggunakan Kombinasi Minyak Chamomile (Matricaria recutita) dan Minyak Mawar (Rosa alba) - Prawesti, Camelia Ayu; Wulansari, Eka; Putri, Salsabila (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Aromatherapy is a form of complementary therapy that utilizes plant-derived essential oils to support physical and mental health. Chamomile essential oil (Matricaria recutita) possesses a characteristic calming aroma and has been reported to exhibit various pharmacological activities, including antipyretic, anti-inflammatory, antispasmodic, and sedative effects. Rose essential oil (Rosa alba) is also known for its antidepressant and anxiolytic properties, as well as its potential to reduce blood pressure and alleviate sleep disorders, migraines, and stress. This study aims to determine the optimal composition of chamomile and rose essential oils in an aromatherapy medicated oil formulation based on its physical characteristics. The formulation employed olive oil and red palm oil as carrier bases due to their high antioxidant content, particularly vitamin E and carotenoids. Optimization was conducted using a Simplex Lattice Design (SLD) approach with eight combination formulations. The prepared formulations were evaluated for pH, specific gravity, and displaced volume. The results demonstrated that the combination of chamomile and rose essential oils significantly influenced the physical characteristics of the formulation. Based on the optimization of physical parameters (pH, specific gravity, and displaced volume) the optimal formulation was obtained with a composition of 1.5% chamomile essential oil and 1.5% rose essential oil. This formulation exhibited acceptable physical characteristics.